HUBUNGAN KARAKTERISTIK TERHADAP TINGKAT KECEMASAN IBU HAMIL MENJELANG PERSALINAN SPONTAN DI PUSKESMAS KECAMATAN MAKASAR JAKARTA TIMUR - Gary1, Wulan Puspa; Hijriyati, Yoanita; Zakiyah, Zakiyah (Fakultas Ilmu Kesehatan Universitas Katolik Musi Charitas, 2020)
The incidence of anxiety in Indonesia in the face of childbirth as many as 107 million pregnant women (28.7%) of 373 million pregnant women who experience anxiety about childbirth. The population of pregnant women on the island of Java in 2012 was 67,976 pregnant women, while those who experienced anxiety at the time of going into labor were 35,587 people (52.3%) (BPS, 2013). Parity of pregnant and work mothers is a factor causing the emergence of anxiety levels in primigravida pregnant women (Handayani, 2015). This study aims to determine how the relationship of characteristics to the level of anxiety of pregnant women before spontaneous labor in the District Health Center Makasar, East Jakarta. This study uses a descriptive correlation design with the Cross Sectional survey method. Data analysis using the Spearman Rank test, this study was conducted on 41 respondents. The results showed a relationship between the characteristics of age, parity status, occupation with anxiety levels of pregnant women, and there was no relationship between the level of education and anxiety levels of pregnant women. The age correlation value (r = 0.758), with a p-value of 0,000 (<0.05), parity status of the correlation value (r = 0.394) with a p-value of 0.011 (<0.05), education level of correlation value ( r = 0.986) with a p-value of 0.003 (<0.05), Work with a correlation value (r = -0.309) with a p-value of 0.049 (<0.05). Suggestion: pregnant women can take advantage of regular health service visits to reduce anxiety levels before delivery.